(untitled) (International Journal of Engineering and Computer Science, 2014)
An image is an artifact that depicts or records visual perception. Object Based Image Retrieval (OBIR) is a technique to find specific object from image database. Similar images can be retrieved from image database by comparing image features. A feature is a piece of information which is relevant for solving the computational task related to a certain application. Visual content of the entire image refer to the global features. Locally rich information like interesting point detection can be addressed in local features. This paper include color features and edge detection feature as global feature and corner detection feature as local feature. Some techniques for finding each features and comparison of those techniques are mentioned here.